Patophysiology of metabolic syndrome in mentally ill patients treated by antipsychotics - Krzewicka-Romaniuk, Ewa; Siedlecka, Dagna; Makuch, Marcelina; Romaniuk, Artur (Journal of Education, Health and Sport, 2019)
The metabolic syndrome is increasingly named as epidemic of our time. It affects about 20-25% of the world’s population and is associated with a twofold increase in the risk of death and a threefold increase in the risk of heart attack and stroke. Numerous scientific studies confirm the more frequent occurrence of the metabolic syndrome among the mentally ill patients than in the general population. It is related not only to common inflammatory etiology of psychiatric disorders and metabolic syndrome, endocrinopathies accompanying mental illness, unhealthy lifestyle of psychiatric patients or genetic predispositions of this group of patients to the development of metabolic disorders, but also with the use of psychiatric drugs such as antipsychotics or mood stabilizers.